2008
DOI: 10.1007/s11605-007-0402-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Long-term Outcome and Prognostic Factors According to Viral Status in Patients with Hepatocellular Carcinoma Treated by Surgery

Abstract: Long-term postoperative survival and prognostic factors were examined retrospectively in patients with hepatocellular carcinoma (HCC) with serum hepatitis B surface antigen (HBsAg) or hepatitis C antibody (HCVAb) and in those without virus infection. Subjects were 265 consecutive HCC patients treated surgically at one institution during the period 1990 to 2006. Postoperative survival was analyzed and compared between HBsAg-positive (B-HCC), HCVAb-positive (C-HCC), and hepatitis B- and C-negative (NBNC-HCC) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…HCCs associated with high AFP level had a higher cell proliferative activity and more aggressive behaviour [20]. In our study, AFP was a significant predictor of HCC recurrence; similar to other studies evaluating HCV related HCCs [3,21] and hepatitis B virus (HBV) related HCCs [13,22]. Hepatocellular carcinoma (HCC) is characterized by its high affinity for vascular invasion (microvascular or microvascular invasion), which indicates aggressive biological manner of the tumour and is currently one of the most grave predictors of HCC recurrence [23].…”
Section: Discussionsupporting
confidence: 89%
“…HCCs associated with high AFP level had a higher cell proliferative activity and more aggressive behaviour [20]. In our study, AFP was a significant predictor of HCC recurrence; similar to other studies evaluating HCV related HCCs [3,21] and hepatitis B virus (HBV) related HCCs [13,22]. Hepatocellular carcinoma (HCC) is characterized by its high affinity for vascular invasion (microvascular or microvascular invasion), which indicates aggressive biological manner of the tumour and is currently one of the most grave predictors of HCC recurrence [23].…”
Section: Discussionsupporting
confidence: 89%
“…These data partly contradict a Japanese retrospective analysis revealing higher overall and progression-free survival for patients with HCC not attributable to HBV or HCV infection [34]. For patients with chronic HBV infection it has been shown that successful treatment of the infection prolongs survival of patients with nonresectable HCC treated by chemoembolization [35], and after curative treatment [36].…”
Section: Discussionmentioning
confidence: 90%
“…14 Previous studies 14,15,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] indicate that early recurrence (i.e., within approximately 2 years of resection) includes both intrahepatic metastases from primary and multicentric lesions, whereas late recurrence (i.e., >2 years after resection) is predominantly of multicentric origin. In the present study, cumulative disease-free survival plateaued 2 years after resection in the NAFLD group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others reported higher frequencies of intrahepatic recurrences and lower survival rates for patients with HCV-related HCC compared to patients infected with hepatitis B virus or with non-B non-C hepatitis. [11][12][13][14][15] There is little information in the literature regarding comparative analyses of surgical outcomes between patients with NAFLD-related HCC and patients with hepatitis virus-related HCC. Thus, there is no consensus concerning differences in surgical outcomes in patients with HCC depending on the underlying liver disease.…”
Section: Introductionmentioning
confidence: 99%